2021
DOI: 10.1097/cce.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

Early Intubation and Increased Coronavirus Disease 2019 Mortality: A Propensity Score–Matched Retrospective Cohort Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Four prospective cohort studies [ 16 , 27 , 31 , 33 ] included 504 patients (sample size range, 32–205), and eight retrospective cohort studies [ 14 , 15 , 17 , 26 , 28 30 , 32 ] included 2,339 patients (sample size range, 39–1618). Six studies [ 14 , 15 , 26 , 28 , 30 , 32 ] were performed in the US, three [ 27 , 31 , 33 ] in Europe, two [ 17 , 29 ] in Asia, and one [ 16 ] in Chile. Seven studies [ 14 – 17 , 26 , 30 , 33 ] were single-center studies, while the others were multi-center studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four prospective cohort studies [ 16 , 27 , 31 , 33 ] included 504 patients (sample size range, 32–205), and eight retrospective cohort studies [ 14 , 15 , 17 , 26 , 28 30 , 32 ] included 2,339 patients (sample size range, 39–1618). Six studies [ 14 , 15 , 26 , 28 , 30 , 32 ] were performed in the US, three [ 27 , 31 , 33 ] in Europe, two [ 17 , 29 ] in Asia, and one [ 16 ] in Chile. Seven studies [ 14 – 17 , 26 , 30 , 33 ] were single-center studies, while the others were multi-center studies.…”
Section: Resultsmentioning
confidence: 99%
“…The index time for intubation was defined according to the onset of acute respiratory failure in five studies [ 15 , 26 , 29 , 30 , 33 ] and ICU admission in three studies [ 17 , 28 , 31 ]. Five studies [ 14 , 26 , 28 , 29 , 31 ] defined early intubation as intubation within 24 h and five studies [ 16 , 17 , 27 , 30 , 32 ] as within 48 h from the index time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus disease 2019 (COVID-19) is a highly contagious infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 1 , 2 ]. It has spread very rapidly around the world, resulting in severe acute respiratory failure with less known pathophysiology [ 2 , 3 , 4 , 5 ]. It has increased its rate of transmission and critical illness with a higher risk of intensive care unit (ICU) admissions, producing a wide spectrum of mortality rates [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported that NIV might not influence the outcome or natural course of COVID-19 disease [ 9 ]. Invasive MV via a tracheal tube appears to be the most common approach after failed NIV but is associated with higher all-cause mortality in COVID-19 patients [ 10 , 11 , 12 ]. Contrasting results have been published regarding early intubation in terms of survival benefits [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%